The Status of Household Food Insecurity: The Case of West Belesa, North Gondar, Amhara Region, Ethiopia - Yehuala, Sisay; Melak, Degsew; Mekuria, Wuletaw (International Journal of Scientific Research and Management (IJSRM), 2018)
The vast majority of extraordinarily poor households live in rural areas that are heavily reliant on rain fed agriculture. In Ethiopia, the Amhara region in particular, has been prone to much suffering in the past, and was one of the hardest hit areas. Different projects and programs were designed and implemented to reduce household food insecurity. However, the effect of the program whether household food insecurity is reduced or not was not yet assessed in these areas. This is therefore, to investigate the current food insecurity status of different households and the determinant factors that affect household food insecurity in the study area. A multi stage sampling method was employed to select 120 respondents from West Belesa Woreda and structured survey questionnaire was designed to collect quantitative data. Data was analyzed using descriptive statistics and econometric model. From the study it was found out that about 35.8% of the respondent households were food insecure and the remaining 64.2% of them were food secure that indicated the reduction of food insecurity status of the people in the study area. Among the different variables hypothesized to affect household food insecurity; family size, total income, distance from market, total livestock holding and losses of crops were found to be significant variables to affect household food insecurity. It can be concluded that because of the intervention of many projects and programs the food insecurity status of the woreda was reduced to 35.8 %. This indicates that the efforts done by the government and non-governmental organizations before the study year were somehow successful. Therefore, Governmental and Non-governmental organizations still have to work more to minimize the food insecurity status of West Belesa in particular and drought prone woredas of the region in general